MENTAL ACCOUNTING AND CONSUMPTIVE BEHAVIOR AS DUAL MEDIATORS BETWEEN FINANCIAL LITERACY AND E-MONEY IN FINANCIAL MANAGEMENT - Nursasi, Enggar; Bunyamin, Bunyamin (JRAK, 2026)
The rapid growth of financial technology raises concerns that e-money may encourage higher consumption. This study aims to examine how mental accounting and consumptive behavior mediated the effects of financial literacy and e-money usage on financial management. A quantitative approach was employed with 216 respondents and analyzed using PLS-SEM. The results showed that financial literacy and e-money positively affected financial management, while consumptive behavior negatively impacted it. Mental accounting positively mediated these relationships, whereas consumptive behavior served as a negative mediator. By integrating both positive and negative behavioral mediators, this study provided a comprehensive understanding of digital finance’s influence on individual financial outcomes. Practically, the findings highlight the importance of embedding educational features in e-money applications to enhance financial literacy and promote better financial management.